2010
DOI: 10.1111/j.1471-6712.2010.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for lifestyle changes to improve health in people with impaired glucose tolerance

Abstract: Persons with IGT appear to benefit from lifestyle changes along four dimensions of motivational significance: Structure and rhythm, Sickness concerns, Activity levels, Social relations. This means that attention needs to be more carefully tailored the individual along these four dimensions than has been the case in traditional health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 28 publications
3
50
0
Order By: Relevance
“…Psycho-physiological approaches including music, experiences of music and dancing also seem to have positive health effect [8, 9], and Hansen et al [10] found that social relations are of significance to motivational health-related behavior. This is in line with studies where social participation (cultural, religious, social activities) was found to be associated with survival, longevity and where also participation in cultural activities might have a positive influence and personal development [11–13].…”
Section: Introductionmentioning
confidence: 99%
“…Psycho-physiological approaches including music, experiences of music and dancing also seem to have positive health effect [8, 9], and Hansen et al [10] found that social relations are of significance to motivational health-related behavior. This is in line with studies where social participation (cultural, religious, social activities) was found to be associated with survival, longevity and where also participation in cultural activities might have a positive influence and personal development [11–13].…”
Section: Introductionmentioning
confidence: 99%
“…Several barriers have been identified for lifestyle behavior change. Some of these are: patients do not regard diabetes as a serious disease [31], misperception of the patients' actual lifestyle behavior [32], decrease in wellbeing [33], asymptomatic disease, increased costs, cultural background [11], patients are satisfied with their behavior [34], frustration from lack of success [35], physical limitations, lack of time [36] and interference with work [37]. In the end however, without being motivated, acquiring and maintaining a healthy lifestyle will probably be impossible.…”
Section: Comparison With Existing Literaturementioning
confidence: 98%
“…The World Health Organization (WHO) estimates that the prevalence of diabetes will more than double from 1997 to 2025 among adults, with an estimated increase from 143 million to 300 million cases. In 2000, the WHO reported a global prevalence of diabetes of 171 million people, and the expected prevalence in 2030 was predicted to be 366 million people [1] [2]. Physical inactivity and increased body weight are expected to increase the prevalence of Type 2 diabetes in Europe from 3.5% to 4.75% in the next 25 years [3] [4].…”
Section: Introductionmentioning
confidence: 99%